Combinations of NOS3 and CYBA alleles and essential hypertension risk in men - P. I. Makarevich; E. Yu. Andreenko; A. V. Balatsky; A. V. Kolotvin; N. O. Popova; E. B. Yarovaya; L. M. Samokhodskaya; V. A. Tkachuk (Кардиоваскулярная терапия и профилактика)
Aim. To study the role of Glu298Asp and C242T point substitutions and their combinations in the development of essential arterial hypertension (AH). Material and methods. The study included 511 men aged 19—61 years (mean age 36,2±5,5 years): 409 patients with confirmed AH diagnosis (main group, MG), and 102 healthy men without cardiovascular disease (control group, CG). Alleles of interest were identified using polymerase chain reaction and restriction fragment length analysis. Results. Among AH patients, the prevalence of mutant allele 298Asp was 22,8 %, vs. 24,2 % in the CG (р>0,05). The prevalence of mutant allele 242Т was 31,8 % and 37,8 % in MG and CG, respectively (p>0,05). The combinations where mutant allele 298Asp outnumbered mutant allele 242Т were shown to increase AH risk. In the binary logistic regression model, AH odds ratio and confidence intervals were calculated. The p value of the model was assessed with maximal likelihood test. In people with “prevalent” NOS3 mutation, AH risk was higher (OR 1,55; 95 %CI 1,00—2,40; p=0,049). Adverse genotypes included 298Het/242Wt; 298Mut/242Het; 298Mut/242Wt и 298Wt/242Het. Conclusion. Point mutations of Glu298Asp and C242T did not increase AH risk in men substantially. However, other genotype combinations, associated with increased AH risk, were identified.